Mathematical modelling of concrete compressive strength with waste tire rubber as fine aggregate - Chong, B. W.; Rokiah, Othman; Putra Jaya, Ramadhansyah; Doh, Shu Ing; Li, Xiaofeng (Faculty Mechanical Engineering, UMP, 2021)
With the increasing number of vehicle due to the boom of population and rapid modernisation, the management of waste tire is growing problem. Reusing grinded tire rubber in concrete is a green innovation which provide an outlet for reusing waste tire. While providing certain benefits to concrete, incorporation of tire rubber results in significant loss of concrete compressive strength which hinders the potential of rubberised concrete. This paper aims to develop mathematical models on the influence of tire rubber replacement on the compressive strength of concrete using design of experiment (DoE). 33 data sets are gathered from available literature on concrete with waste tire rubber as partial replacement of fine aggregate. Response surface methodology (RSM) model of rubberised concrete compressive strength shows great accuracy with coefficient of determination (R2) of 0.9923 and root-mean-square error (RMSE) of 2.368. Regression analysis on the strength index of rubberised concrete shows that rubberised concrete strength loss can be expressed in an exponential function of percentage of replacement. The strength loss is attributed to morphology of rubber particles and the weak bonds between rubber particles and cement paste. Hence, tire rubber replacement should be done sparingly with proper treatment and control to minimise concrete strength loss.